Cobalt-phosphorus co-doped improved carbon nitride material as well as preparation method and application thereof
CoPCN materials were prepared by using cobalt-phosphorus co-doping and in-situ photodeposition technology in carbon nitride materials, which solved the problem of inefficiency of existing carbon nitride materials in the photocatalytic synthesis of hydrogen peroxide, and achieved high efficiency , stable and economical photocatalytic synthesis of H2O2 effects.
Patent Information
- Application Number
- CN202411586697.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-18
AI Technical Summary
Existing carbon nitride materials have limitations in the rapid recombination of photogenerated carriers, solar light absorption range and conversion efficiency during the photocatalytic synthesis of hydrogen peroxide, and the use of sacrificial agents is often required to improve reaction rate and selectivity, which increases the Cost and processing difficulty.
Cobalt-phosphorus co-doped improved carbon nitride material (CoPCN) is prepared through in-situ photodeposition technology. This material optimizes the energy band structure and light absorption range through the synergistic effect of cobalt single-atom loading and phosphorus doping, and improves light Catalytic activity and selectivity, and no additional sacrificial agent is required under pure water conditions.
It has achieved efficient photocatalytic synthesis of hydrogen peroxide without sacrificing agents, significantly improved the H2O2 generation rate, and improved the stability and recycling of materials, with wide application potential in water treatment and green chemical synthesis. .
Smart Images

Figure CN119456007A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of photocatalysis, and in particular to an improved carbon nitride material co-doped with cobalt and phosphorus, and a preparation method and application thereof. Background Art
[0002] Carbon nitride (CN), as a metal-free two-dimensional material, has shown great potential as a promising candidate for photocatalytic synthesis of hydrogen peroxide (H2O2) due to its excellent in-plane charge carrier mobility, high catalytic active sites, and easy element doping capability. 2 O 2 ) has a broad prospect as a potential candidate material for CN. CN materials have won wide attention from scientific research and industry due to their low cost, high chemical stability and simple preparation process.
[0003] Despite this, CN materials still have certain limitations in terms of rapid recombination of photogenerated carriers, solar light absorption range, and solar light conversion efficiency. In order to overcome these challenges, the heteroatom doping strategy is adopted to modify CN materials, which shows great potential. This strategy can not only significantly adjust the band structure of CN materials, but also effectively improve their light response ability and photocatalytic activity, thereby enhancing their selectivity.
[0004] The photocatalytic performance of CN materials has been significantly optimized through carefully designed heteroatom doping, making them suitable for photocatalytic H production. 2 O 2 The improvement of this material provides new ideas and methods for realizing efficient, economical and environmentally friendly photocatalytic technology.
[0005] Zhang Jinlong and his team's breakthrough research revealed the significant optimization effect of phosphorus (P) doping on the band structure of carbon nitride (CN) materials. This optimization not only adjusts the electronic structure of CN, but also adjusts the hydrogen peroxide (H 2 O 2 ) is transformed from a single-electron pathway to a more thermodynamically favorable two-electron pathway. The results show that the doped catalyst H 2 O 2 The production rate increased sharply to 1083 μmol g -1 h -1 , a value that is nearly 7 times that of the original CN material, marking it as one of the most active photocatalysts currently available.
[0006] Xu Hui and his colleagues successfully prepared phosphorus-oxygen modified cyanide-rich carbon nitride (CNOP) using sodium phosphate-assisted high-temperature calcination technology. This material showed significant improvements in visible light utilization, optimization of electronic reaction pathways, and two-electron oxygen reduction reaction (ORR) selectivity, showing excellent H 2 O 2Especially at 550nm wavelength, CNOP can still maintain high efficiency of H 2 O 2 The yield is 17 times higher than that of the original CN material.
[0007] Globally, single atom catalysts (SACs) have attracted widespread attention in the field of photocatalysis. SACs, with their isolated metal atoms as catalytic centers, are fixed on substrates with different coordination environments, showing excellent catalytic activity, selectivity, and atomic utilization. For CN materials, their potential in catalytic reactions can be greatly improved by anchoring single metal atoms on nitrogen-functionalized carbon matrices. Nitrogen atoms form stable bonds with metal atoms, optimize active sites, and improve the electronic environment of metal single atoms.
[0008] Wang Ning et al. further anchored cobalt atoms on a two-dimensional sulfur-doped carbon nitride / reduced graphene oxide (Co-CN@G) heterostructure, achieving efficient H removal in natural seawater. 2 O 2 Photocatalytic synthesis. This synergistic effect of single atoms and heterostructures not only effectively inhibits the recombination of photogenerated carriers, but also introduces a photothermal effect, reduces the reaction energy barriers of oxygen reduction and water oxidation, and accelerates the reaction kinetics. Co-CN@G exhibits excellent photocatalytic performance without the need for sacrificial agents, providing a new direction for the development of photocatalytic technology.
[0009] In the above research on photocatalytic technology, the research on phosphorus-doped carbon nitride (CN) materials by Zhang Jinlong's team and the research on phosphorus-oxygen-modified cyanide-rich carbon nitride (CNOP) by Xu Hui and others have shown significant improvements in photocatalytic activity. These technologies improve the separation efficiency and reaction kinetics of photogenerated charges by changing the energy band structure and surface properties of the materials. However, the photocatalytic processes in these studies usually require sacrificial agents to increase the reaction rate or selectivity, which increases costs and processing difficulties.
[0010] In addition, although CN materials have good chemical stability, their stability and recycling ability in long-term photocatalytic processes still need further research and improvement. Because maintaining high stability under long-term illumination conditions is the key to achieving commercial applications. Under actual environmental conditions, factors such as natural light changes and temperature fluctuations may affect the performance of photocatalysts, and further research is needed to ensure stability and efficiency under variable conditions.
[0011] Therefore, it is also necessary to comprehensively consider material design, synthesis methods, structural regulation, and matching with actual application conditions under pure water conditions to achieve efficient, stable, and economical photocatalytic synthesis of H 2 O 2 technology. Summary of the invention
[0012] In order to solve the above technical problems, the present invention provides a cobalt-phosphorus co-doped improved carbon nitride material and its preparation method and application. The present invention prepares cobalt-phosphorus doped improved graphite phase carbon nitride (CoPCN) by in-situ photodeposition. The preparation process is simple, which not only improves the synthesis efficiency of the material, but also provides a new perspective for in-depth understanding of the relationship between material characteristics and performance.
[0013] The present invention does not require the use of sacrificial agents, which reduces the reaction cost, simplifies the reaction system, and may reduce the subsequent processing steps. The photocatalytic reaction carried out under pure water conditions avoids potential pollution to the environment and conforms to the principles of green chemistry. Although no sacrificial agent is used, the photocatalytic system of the present invention still exhibits efficient H 2 O 2 The generation rate shows that the material itself has excellent photocatalytic activity. The photocatalytic reaction under pure water conditions reduces the use of chemical additives and is more environmentally friendly. In addition, due to its environmental friendliness and high efficiency, the technology of the present invention has wide application potential in water treatment and green chemical synthesis.
[0014] The present invention is achieved through the following technical solutions:
[0015] The first object of the present invention is to provide a method for preparing a cobalt-phosphorus co-doped improved carbon nitride material, comprising the following steps:
[0016] (1) subjecting urea to a thermal polymerization reaction to synthesize two-dimensional carbon nitride nanosheets;
[0017] (2) mixing the two-dimensional carbon nitride nanosheets prepared in step (1) with sodium hypophosphite monohydrate, grinding them, and then calcining them under a protective atmosphere to obtain carbon nitride phosphide nanosheets;
[0018] (3) dispersing the carbon nitride phosphide nanosheets obtained in step (2) in an aqueous solution containing an alcohol, adding cobalt salt and sodium hypophosphite and mixing evenly to obtain a mixed solution;
[0019] (4) Under a protective atmosphere, the mixed solution obtained in step (3) is irradiated under a xenon lamp to achieve in-situ deposition of cobalt; the reaction solution after irradiation is washed and dried to obtain a cobalt-phosphorus co-doped improved carbon nitride material.
[0020] In one embodiment of the present invention, in step (1), the two-dimensional carbon nitride nanosheets are obtained by thermal polymerization of urea;
[0021] And / or, the thermal polymerization reaction is a three-stage calcination: the first temperature is raised to 545°C-555°C and maintained for 3.92h-4.08h, and then cooled to room temperature; the second temperature is raised to 545°C-555°C and maintained for 0.92h-1.08h, and then cooled to room temperature; the third temperature is raised to 545°C-555°C and maintained for 0.92h-1.08h.
[0022] And / or, the first heating rate is 1.5°C / min to 2.5°C / min; the second heating rate is 4.5°C / min to 5.5°C / min; the third heating rate is 1.5°C / min to 2.5°C / min.
[0023] In one embodiment of the present invention, in step (2), the ratio of the two-dimensional carbon nitride nanosheets to sodium hypophosphite monohydrate is 24:51 to 49:26, preferably 1:0.5.
[0024] In one embodiment of the present invention, in step (2), the calcination conditions are: calcination at 295° C. to 305° C. for 1.92 h to 2.08 h.
[0025] In one embodiment of the present invention, in step (3), the mass ratio of the carbon nitride phosphide nanosheets to the cobalt salt is 49:11 to 51:9, preferably 5:1.
[0026] In one embodiment of the present invention, in step (3), the cobalt salt is selected from cobalt chloride hexahydrate and / or cobalt nitrate hexahydrate.
[0027] In one embodiment of the present invention, in step (3), the alcohol is selected from methanol, ethanol and isopropanol, etc.; the content of the alcohol is 20%. Methanol is preferred in the present invention, and methanol has some unique advantages compared with other alcohols. First, methanol is a strong polar solvent, and its polarity order is higher in common solvents, which enables it to better dissolve many inorganic salts and organic compounds, thereby helping to improve the efficiency of the photocatalytic reaction.
[0028] In one embodiment of the present invention, in step (3), the power of the illumination is 295W to 305W, and the time is 5min to 15min.
[0029] The second object of the present invention is to provide a cobalt-phosphorus co-doped carbon nitride material prepared by the preparation method.
[0030] The third object of the present invention is to provide the use of the cobalt-phosphorus co-doped improved carbon nitride material in the photocatalytic synthesis of hydrogen peroxide.
[0031] In one embodiment of the present invention, the wavelength of the light source in the photocatalysis is 365nm-420nm.
[0032] The purpose of the present invention is to provide the application of the improved carbon nitride material co-doped with cobalt and phosphorus in the photocatalytic synthesis of hydrogen peroxide.
[0033] In one embodiment of the present invention, the wavelength of the light source in the photocatalysis is 365nm-420nm.
[0034] The phosphating heat treatment of the present invention is to use sodium hypophosphite to phosphate CN, which is a prerequisite for obtaining PCN. Cobalt phosphorus-doped carbon nitride (CoPCN) is prepared on PCN using photoreduction technology, which can form metal sites on the semiconductor surface under mild conditions.
[0035] The cobalt metal in the improved carbon nitride material co-doped with cobalt and phosphorus in the present invention exists in the form of a single atom, and the active sites of CN are increased through the Co-N bond. This single atom dispersion technology is the key to improving catalytic performance. Phosphorus doping significantly increases the light absorption range of CN and reduces the band gap. This doping ratio and method are important links in optimizing the energy band structure. And the photoelectrochemical test results show that the material can effectively promote charge separation and accelerate charge transfer. These properties are crucial to improving photocatalytic efficiency. In addition, CoPCN has good hydrophilicity and H 2 O 2 These characteristics help to improve the photocatalytic synthesis of H 2 O 2 selectivity and efficiency.
[0036] The improved carbon nitride material co-doped with cobalt and phosphorus can efficiently photocatalyze the synthesis of H in pure water without the need for an additional sacrificial agent. 2 O 2 The synergistic effect of phosphorus doping and cobalt single atom loading improves the photocatalytic activity and promotes the selective synthesis of H 2 O 2 This synergistic effect is the key innovation to improve performance. 365nm Under this condition, CoPCN exhibits efficient H 2 O 2 The synthesis rate reached 160.24 μmol L - 1 h -1 , which is 4.8 times that of CN, showing its excellent photocatalytic performance.
[0037] The above technical solution of the present invention has the following advantages compared with the prior art:
[0038] The present invention provides a cobalt-phosphorus co-doped improved carbon nitride material and its preparation method and application. The cobalt-phosphorus co-doped improved carbon nitride material of the present invention effectively broadens the light absorption range of graphite phase carbon nitride; adjusts the energy band structure of CoPCN; increases the specific surface area and active sites; increases the quantum efficiency and solar-chemical energy conversion efficiency; enhances the stability and recyclability of the material; improves the catalytic activity and selectivity; and realizes green chemistry and sustainable development.
[0039] In addition, the cobalt-phosphorus co-doped improved carbon nitride material of the present invention can be used as a photocatalytic material with superior performance, high cost-effectiveness and environmental friendliness; it can be used for the efficient synthesis of H 2 O 2 , promoting the application of photocatalytic technology in fields such as energy conversion and environmental purification. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments of the present invention in conjunction with the accompanying drawings, wherein:
[0041] Figure 1 Schematic diagram of the synthesis process of the photocatalyst CoPCN in an embodiment of the present invention;
[0042] Figure 2 are (a) XRD and (b) FT-IR spectra of all photocatalysts in the embodiments of the present invention;
[0043] Figure 3 are SEM images (ab) of CN and PCN and TEM images (cd) of CN and CoPCN in the embodiments of the present invention;
[0044] Figure 4 The HAADF-STEM images (ab) of the photocatalyst CoPCN under high magnification and the element mapping of C, N, P and Co in the EDS spectrum (c) in the embodiment of the present invention are shown;
[0045] Figure 5 is the N of CN and CoPCN in the embodiment of the present invention 2 Adsorption-desorption isotherms and pore size distribution;
[0046] Figure 6 The CN and CoPCN in pure water and 10% H 2 O 2 Contact angle in aqueous solution;
[0047] Figure 7 1 is the photocurrent spectrum (a) and impedance spectrum (b) of all samples in the embodiments of the present invention;
[0048] Figure 8It is the monochromatic LED in the application example of the present invention. 420nm All samples produced H in 2 h. 2 O 2 Performance graph (a); all samples under monochromatic LED 365nm Generate H 2 O 2 (b) All samples generate H under simulated sunlight AM 1.5G. 2 O 2 Comparison of the rates of CoPCN samples at different catalyst contents (c); H generation at different reaction temperatures 2 O 2 Rate comparison (e); Photocatalytic H production under different atmosphere conditions in pure water 2 O 2 Performance comparison (f);
[0049] Fig. 9 The monochromatic LED in the application example of the present invention 365nm Photocatalytic H production of samples prepared under different schemes within 2 hours 2 O 2 Performance diagram (a) and generated H 2 O 2 Rate comparison (b);
[0050] Fig.10 This is a photocatalytic test chart of CoPCN after 4 cycles (12h) in the application example of the present invention. DETAILED DESCRIPTION
[0051] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0052] Example 1
[0053] This embodiment provides a method for preparing a cobalt-phosphorus co-doped improved carbon nitride material (the schematic diagram of the preparation process is shown in FIG. Figure 1 The specific steps are as follows:
[0054] 1. The two-dimensional CN nanosheets were prepared by three-step thermal polymerization technology. The specific synthesis process is as follows:
[0055] (1) Initial calcination stage: A crucible containing 15 g of urea was placed in a muffle furnace and slowly heated to 550°C at a heating rate of 2°C / min. Urea was calcined at 550°C for 4 h to ensure that it was fully pyrolyzed. After the first calcination, the crucible was allowed to cool naturally to room temperature to avoid damage to the material structure due to rapid temperature changes.
[0056] (2) Secondary calcination: The cooled crucible was heated at a rate of 5°C / min to 550°C and maintained at high temperature for 1 hour, and then cooled naturally to room temperature.
[0057] (3) Final calcination: After cooling to room temperature for the second time, the heating and calcination process was repeated for the third time at a heating rate of 5°C / min, also at 550°C for 1 hour.
[0058] After completing all the above calcination steps, the crucible was cooled to room temperature again to obtain a light yellow 2D CN nanosheet sample, which was labeled as CN.
[0059] 2 Preparation of phosphide carbon nitride (PCN) nanosheets:
[0060] The obtained CN was mixed with sodium hypophosphite monohydrate in a ratio of 1:0.5, and after being fully and evenly mixed, it was placed in a dry mortar for fine grinding. The ground sample was placed in a porcelain boat and tightly wrapped with tin foil to prevent any impurities from being incorporated. Then, in a tube furnace filled with argon, the sample was calcined at 300°C for 2h at a heating rate of 2°C / min. After calcination, the sample was naturally cooled to room temperature and then washed three times in succession with deionized water to remove possible residual impurities. Finally, the washed sample was placed in a vacuum drying oven and dried under mild conditions at 60°C to obtain PCN nanosheets.
[0061] 3. In-situ photodeposition technology was used to prepare cobalt phosphorus carbon nitrogen (CoPCN) composite materials:
[0062] First, 100 mg of the obtained PCN was dispersed in 50 mL of a deionized water solution containing 20% (volume percentage) methanol and dissolved by ultrasonic treatment. Subsequently, 20.187 mg of cobalt chloride hexahydrate (for 100 mg PCN, the addition amount of Co was 5%) and 63 mg of sodium hypophosphite were added, and ultrasonic stirring was continued to ensure uniform mixing. In an argon atmosphere, the resulting mixed solution was exposed to a 300 W xenon lamp for 10 minutes to achieve in-situ deposition of cobalt. After illumination, the reaction solution was collected and washed alternately with ethanol and deionized water 6 times to remove unreacted precursors and by-products. The washed solution was dried in a vacuum oven to obtain a light yellow powdery CoPCN composite material, and the sample was labeled as 5% CoPCN.
[0063] Example 2
[0064] This embodiment provides a method for preparing a cobalt-phosphorus co-doped improved carbon nitride material, which is similar to the embodiment 1, except that: for 100 mg PCN, the mass of 3% Co is 3 mg, and the amount of cobalt chloride hexahydrate added is 12.11 mg (the relative molecular weight of Co is 58.93, CoCl2 6H 2 The relative molecular mass of O is 237.93), and the sample is labeled as 3% CoPCN.
[0065] Example 3
[0066] This embodiment provides a method for preparing a cobalt-phosphorus co-doped improved carbon nitride material, which is similar to Example 1, except that for 100 mg PCN, the mass of 10% Co is 10 mg, and the amount of cobalt chloride hexahydrate added is 40.375 mg according to the molecular molar mass conversion, and the sample is marked as 10% CoPCN.
[0067] Example 4
[0068] This embodiment provides a method for preparing a cobalt-phosphorus co-doped improved carbon nitride material, which is similar to Example 1, except that for 100 mg PCN, the mass of 20% Co is 20 mg, and the amount of cobalt chloride hexahydrate added is 80.75 mg according to the molecular molar mass conversion, and the sample is marked as 20% CoPCN.
[0069] Example 5
[0070] This embodiment provides a method for preparing a cobalt-phosphorus co-doped improved carbon nitride material, which is similar to Example 1, except that for 100 mg PCN, the mass of 30% Co is 30 mg, and the amount of cobalt chloride hexahydrate added is 121.125 mg according to the molecular molar mass conversion, and the sample is marked as 30% CoPCN.
[0071] Related tests:
[0072] (1) X-ray diffraction (XRD) analysis was used to investigate the crystal and phase structures of CN, PCN, and CoPCN samples with different cobalt contents. Figure 2 As shown in (a): The CN sample exhibits characteristic peaks at 13.4° and 27.3°, corresponding to the (100) and (002) crystal planes, respectively, revealing the ordered planar arrangement of its triazine units and the typical graphite-type stacking structure. Phosphorus doping leads to a weakening of the (100) peak, indicating that the heptazine unit structure is distorted. No peaks belonging to Co metal are observed in the XRD spectrum of CoPCN, confirming the uniform dispersion of cobalt species in the sample and the absence of cobalt nanoparticles.
[0073] (2) Figure 2 As shown in (b), the molecular structure of the sample was studied by Fourier transform infrared spectroscopy (FTIR): the FTIR spectrum of the PCN sample is similar to that of CN, indicating that the framework structure of CN remains unchanged during the phosphorus doping process. The characteristic vibration peak of the triazine unit is located at 807 cm -1, and 3000-3500cm -1 The broad band at 900 cm is attributed to the stretching vibration of NH / OH. -1 and 1800cm -1 The peaks at 3000 cm-1 correspond to the stretching vibrations of CN and C=N, respectively. -1 Up to 3600cm -1 The broad absorption band between is usually associated with NH stretching vibration or water adsorption. The CoPCN samples with different cobalt contents showed a similar basic structure to CN in FTIR analysis, and no obvious changes were found.
[0074] (3) Figure 3 As shown in the figure, the morphology of the prepared CoPCN samples was analyzed by scanning electron microscopy (SEM) and transmission electron microscopy (TEM): the CN sample showed a typical two-dimensional (2D) layered structure, in which carbon (C) and nitrogen (N) elements were evenly distributed. The morphology of the PCN sample after phosphating treatment changed significantly, forming a block stacking structure, but its original two-dimensional layered structure was well preserved. Cobalt-phosphorus co-doped CoPCN also showed a two-dimensional nanosheet structure similar to CN.
[0075] (4) TEM images further reveal the microstructure of the CoPCN sample, showing a clear transparent layered structure, and no accumulation of nanoparticles or clusters was observed on the surface. In-depth characterization by aberration-corrected high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) is shown in Figure 4 , the present invention observed that Co atoms were uniformly dispersed in the PCN support in the form of bright spots at the atomic scale, indicating that cobalt mainly exists in the form of single atoms. The elemental mapping images of the X-ray energy dispersive spectrometer (EDS) provided conclusive evidence for the uniform distribution of Co atoms on the PCN support. These findings clearly pointed out that the cobalt (Co) species were highly dispersed on the PCN nanosheets and existed in the form of isolated single atoms, which provided favorable conditions for improving the catalytic performance of the material.
[0076] (5) The present invention uses the Brunauer-Emmett-Teller (BET) method to accurately measure the specific surface area of CoPCN and the original CN sample. The results show that the specific surface area of CoPCN is 35.77 m 2 / g, while the specific surface area of original CN is slightly higher, which is 36.34m 2 This data shows that CoP-doped CoPCN successfully maintains the hierarchical nanosheet structure of the original CN, and the two have similar specific surface areas.
[0077] (6) Figure 5As shown in Figure 1, the nitrogen adsorption-desorption isotherm of CoPCN exhibits type IV curve characteristics, which is a typical sign of mesoporous materials. The pore size distribution curve (BJH method) further reveals that the pore size is mainly concentrated in the range of 10nm to 50nm, confirming the existence of mesopores. In addition, the distribution of macropores was observed in the image, indicating that CoPCN has a multi-level pore structure, which may help improve its performance in applications such as catalysis.
[0078] (7) Photocatalytic synthesis of hydrogen peroxide (H 2 O 2 ) is closely related to the hydrophilicity of the photocatalyst. Figure 6 As shown in Figure 2, the contact angle of CoPCN in pure water is 6°, which is closer to 0° than the 10° of pristine CN, indicating that CoPCN has a higher hydrophilicity. This enhanced hydrophilicity may reduce the number of hydrogen bonds, thereby facilitating the formation of H 2 O 2 desorption process.
[0079] For 10% H 2 O 2 The contact angle of CoPCN increased to 27°, while that of CN was 19°. 2 O 2 The high contact angle in solution further confirms its excellent H 2 O 2 Desorption capacity is an important indicator of photocatalyst performance. This excellent desorption capacity helps to improve the photocatalytic synthesis of H 2 O 2 rate and selectivity.
[0080] (8) Figure 7 (a) in the figure shows the time-varying photocurrent intensity curves of CN, PCN and CoPCN samples with different proportions. It was observed that when illuminated, the sample generated photogenerated carriers, resulting in an increase in current density; after the illumination stopped, the generation of carriers was interrupted and the current density dropped rapidly. This phenomenon shows that the level of transient photocurrent is a direct reflection of the efficiency of photoinduced carrier separation. Among them, 5% CoPCN exhibited the highest photocurrent density, significantly exceeding CN, PCN and other CoPCN samples with cobalt content, revealing that the synergistic effect of phosphorus doping and cobalt doping effectively promoted the separation of electrons and holes.
[0081] also, Figure 7This is further confirmed by the electrochemical impedance spectroscopy (EIS) curve (b). In the Nyquist plot of EIS, the radius of the arc represents the size of the interface transfer resistance. The smaller the radius, the faster the interface charge transfer. The experimental results show that 5% CoPCN has the smallest Nyquist arc radius, indicating that its interface resistance is the lowest and the charge transfer rate is the fastest.
[0082] In summary, the CoPCN materials co-doped with cobalt and phosphorus have excellent properties in terms of crystal structure, molecular structure, micromorphology, specific surface area, pore structure, hydrophilicity, H 2 O 2 The photocatalytic performance of the photocatalyst is improved by the optimized desorption capacity, charge carrier separation and transfer, which together promote its application in photocatalytic H synthesis. 2 O 2 Therefore, CoPCN is a photocatalytic material with high potential for efficient and environmentally friendly H 2 O 2 Production.
[0083] Comparative Example 1
[0084] This comparative example provides a Co / CN sample obtained by simple mechanical mixing of Co and CN, and the specific steps are as follows:
[0085] 100 mg of the obtained CN was dispersed in 50 mL of a solution containing 20% methanol and dissolved by ultrasonic treatment. Subsequently, 20 mg of cobalt chloride hexahydrate and 63 mg of sodium hypophosphite were added, and ultrasonic stirring was continued to ensure uniform mixing. The entire process was carried out in the air at room temperature. After about 1 h of ultrasonic stirring for 1 h, the dissolved sample solution was placed in a centrifuge for centrifugation, and the sample was washed with water for 3 consecutive times to obtain the sample, which was placed in a vacuum oven at 60 ° C and dried for 6 h to obtain a Co / CN composite sample.
[0086] The photocatalytic performance of Co / CN obtained in this comparative example is similar to that of CN, which may be because physical mixing fails to effectively activate the Co sites.
[0087] Comparative Example 2
[0088] This comparative example provides a Co / PCN sample obtained by mechanically mixing Co and PCN, and the specific steps are as follows:
[0089] 100 mg of the obtained PCN was dispersed in 50 mL of a solution containing 20% methanol and dissolved by ultrasonic treatment. Subsequently, 20 mg of cobalt chloride hexahydrate and 63 mg of sodium hypophosphite were added, and ultrasonic stirring was continued to ensure uniform mixing. The entire process was carried out in the air at room temperature. After about 1 h of ultrasonic stirring for 1 h, the dissolved sample solution was centrifuged and washed with water for 3 consecutive times to obtain a sample, which was placed in a vacuum oven at 60 ° C and dried for 6 h to obtain a Co / PCN composite sample.
[0090] Application Example 1
[0091] like Figure 8 As shown in the figure, the photocatalytic H production of CN, PCN and CoPCN samples with different cobalt contents under pure water and saturated oxygen conditions was compared under 420nm monochromatic LED irradiation. 2 O 2 The experimental results show that the photocatalytic activity of pure CN is the lowest, while H 2 O 2 The generation rate was 31.15 μmol L -1 h -1 The photocatalytic performance of CoPCN increases with the increase of cobalt content. When the cobalt content is 5wt.%, H 2 O 2 The generation rate reaches a maximum of 303.13 μmol, which is nearly 5 times that of pure CN. However, excessive cobalt leads to a decrease in performance, which may be due to the agglomeration of metal particles or the coverage of photocatalytic active sites.
[0092] Through a series of controlled experiments, the present invention confirmed the necessity of light, oxygen and catalyst in the photocatalytic system. Under 365nm light conditions, CoPCN showed the highest photocatalytic performance, H 2 O 2 The generation rate reached 160.24 μmol L -1 h -1 Increasing the catalyst content and the reaction temperature can significantly improve the photocatalytic efficiency. 2 Atmosphere switched to N 2 When H 2 O 2 The production of oxygen decreased dramatically, confirming the role of oxygen in photosynthetic H 2 O 2 Under anaerobic conditions, even if N 2 No H was detected 2 O 2 The generation of oxygen further confirms the necessity of oxygen.
[0093] Application Example 2
[0094] The present invention evaluates the photocatalytic performance of CoPCN samples obtained by different synthesis methods. Fig. 9 As shown in Figure 2, the Co / CN sample (comparative example) obtained by simple mechanical mixing of Co and CN has a photocatalytic performance similar to that of CN, which may be because physical mixing fails to effectively activate the Co sites. Similarly, the performance of the Co / PCN sample obtained by mechanical mixing of Co and PCN does not exceed that of PCN, indicating that the simple mixing method is not sufficient to improve the photocatalytic activity.
[0095] In contrast, photoreduction is a technique that forms metal sites on the semiconductor surface under mild conditions by irradiating light. The CoPCN samples prepared by photoreduction significantly improved the photocatalytic synthesis of H 2 O 2 This improvement is attributed to the photoreduction method's ability to effectively fix Co atoms, thereby providing more active sites during the photocatalytic process.
[0096] Application Example 3
[0097] Under 420nm monochromatic LED irradiation, CoPCN was subjected to 4 cycles (12h) of photocatalytic testing. The results are as follows: Fig.10 It can be seen that the CoPCN prepared by the present invention is stable in the cyclic photocatalytic process and can be recycled.
[0098] In summary, the CoPCN samples of the present invention have good photocatalytic performance in the synthesis of H 2 O 2 It shows excellent performance in various aspects, providing a valuable reference for the development of efficient photocatalysts.
[0099] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.
Claims
1. A method for preparing a cobalt-phosphorus co-doped improved carbon nitride material, characterized in that: The following steps are involved: (1) subjecting urea to a thermal polymerization reaction to synthesize two-dimensional carbon nitride nanosheets; (2) mixing the two-dimensional carbon nitride nanosheets prepared in step (1) with sodium hypophosphite monohydrate, grinding them, and then calcining them under a protective atmosphere to obtain carbon nitride phosphide nanosheets; (3) dispersing the carbon nitride phosphide nanosheets obtained in step (2) in an aqueous solution containing an alcohol, adding cobalt salt and sodium hypophosphite and mixing evenly to obtain a mixed solution; (4) Under a protective atmosphere, the mixed solution obtained in step (3) is irradiated under a xenon lamp to achieve in-situ deposition of cobalt; the reaction solution after irradiation is washed and dried to obtain a cobalt-phosphorus co-doped improved carbon nitride material.
2. The preparation method according to claim 1, characterized in that: In step (1), the two-dimensional carbon nitride nanosheets are obtained by thermal polymerization of urea; And / or, the thermal polymerization reaction is a three-stage calcination: the first temperature is raised to 545°C-555°C and maintained for 3.92h-4.08h, and then cooled to room temperature; the second temperature is raised to 545°C-555°C and maintained for 0.92h-1.08h, and then cooled to room temperature; the third temperature is raised to 545°C-555°C and maintained for 0.92h-1.08h. And / or, the first heating rate is 1.5°C / min to 2.5°C / min; the second heating rate is 4.5°C / min to 5.5°C / min; the third heating rate is 1.5°C / min to 2.5°C / min.
3. The preparation method according to claim 1, characterized in that: In step (2), the ratio of the two-dimensional carbon nitride nanosheets to sodium hypophosphite monohydrate is 24:51 to 49:
26.
4. The preparation method according to claim 1, characterized in that: In step (2), the calcination conditions are: calcination at 295°C to 305°C for 1.92h to 2.08h.
5. The preparation method according to claim 1, characterized in that: In step (3), the mass ratio of the carbon nitride phosphide nanosheets to the cobalt salt is 49:11 to 51:
9.
6. The preparation method according to claim 1, characterized in that: In step (3), the cobalt salt is selected from cobalt chloride hexahydrate and / or cobalt nitrate hexahydrate.
7. The preparation method according to claim 1, characterized in that: In step (3), the power of the illumination is 295W to 305W, and the time is 5min to 15min.
8. The improved carbon nitride material co-doped with cobalt and phosphorus prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the cobalt-phosphorus co-doped improved carbon nitride material according to claim 8 in photocatalytic synthesis of hydrogen peroxide.
10. The use according to claim 9, characterized in that: The wavelength of the light source in the photocatalysis is 365nm-420nm.